La vie qui bat: Steve Reich’s Drumming and Dance Choreography - Huang, Aiyun (Circuit, 2017)
The music of Steve Reich has been widely written about. In this article I will focus on choreographies set to live performances of Drumming (1971). Drumming is perhaps Reich’s most important early work and a culmination of his various musical explorations and compositional techniques. I have selected three choreographers: Laura Dean, creator of the first choreography set to the music of Drumming (1972); Anne Teresa De Keersmaeker, a choreographer whose works such as Drumming (1998) share Reich’s underlying principle of structures as processes; and Ginette Laurin, whose La vie qui bat (1999) was a joint production between Montreal dance company O Vertigo and the Société de musique contemporaine du Québec (smcq). As this issue celebrates smcq’s 50th anniversary, this article will center on the making and performance practice of La vie qui bat. In preparing this article, the author interviewed Russell Hartenberger (Steve Reich and Musicians), Ginette Laurin, and Walter Boudreau (Artistic Director of the smcq).